2009
DOI: 10.1029/2008jd011224
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of simulated wet deposition of mercury from the North American Mercury Model Intercomparison Study

Abstract: [1] A previous intercomparison of atmospheric mercury models in North America has been extended to compare simulated and observed wet deposition of mercury. Three regional-scale atmospheric mercury models were tested: the Community Multiscale Air Quality (CMAQ) model, the Regional Modeling System for Aerosols and Deposition (REMSAD), and the Trace Element Analysis Model (TEAM). These models were each employed using three sets of lateral boundary conditions to test their sensitivity to intercontinental transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 16 publications
9
42
0
Order By: Relevance
“…Both MDN and EMEP have been used extensively to test atmospheric mercury models (e.g. Bullock et al, 2009;Gusev et al, 2009) and to evaluate the impact of mercury emission reductions (e.g. Butler et al, 2008;Wangberg et al, 2007;Pacyna et al, 2009;Prestbo and Gay, 2009).…”
Section: Testing Oxidation Chemistry Through Antarctic Subsidence Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both MDN and EMEP have been used extensively to test atmospheric mercury models (e.g. Bullock et al, 2009;Gusev et al, 2009) and to evaluate the impact of mercury emission reductions (e.g. Butler et al, 2008;Wangberg et al, 2007;Pacyna et al, 2009;Prestbo and Gay, 2009).…”
Section: Testing Oxidation Chemistry Through Antarctic Subsidence Eventsmentioning
confidence: 99%
“…The above model studies derived their tropospheric bromine concentrations from satellite observations of BrO columns (Chance, 1998;Burrows et al, 1999), which feature polar maxima of BrO. Recent aircraft observations in the Arctic, however, show that the troposphere contributes less to these polar maxima than previously expected (Salawitch et al, 2010), so earlier models likely overestimated tropospheric Hg 0 oxidation at high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review Ariya et al (2015) give a exhaustive summary of modelling progress and of the uncertainties still present concerning the atmospheric Hg cycle. To date only a limited number of model-to-model intercomparisons have been carried out (for the US: Bullock et al, 2008Bullock et al, , 2009Zhang et al, 2012;for Europe: Ryaboshapko et al, 2007; for global models: Travnikov et al, 2010Travnikov et al, , 2016AMAP/UNEP, 2013), where it was found that are often significant differences in Hg concentrations and deposition estimated by different models. Previous European studies (Ryaboshapko et al, 2007) performed a model intercomparison for the year 1999, using eight different models and data from 11 measurement stations with the aim to characterise the ability of CTMs to predict atmospheric Hg concentration and deposition fields.…”
Section: Introductionmentioning
confidence: 99%
“…A significant problem with this approach, however, is that the regional and global models often use different assumptions about Hg emissions, chemistry, deposition, and meteorology. Use of different global models to define boundary conditions leads to large variations in regional patterns of atmospheric Hg concentrations, as well as wet and dry deposition (Bullock et al, 2008(Bullock et al, , 2009Pongprueksa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%